VD_FINDINFO HC / 2012 / 113 vom 1. Februar 2012 - VD Tribunal cantonal (2012)
LÉGITIMATION ACTIVE ET PASSIVE, CONTRAT DE TRAVAIL, COMPENSATION DE CRÉANCES | 124 al. 1 CO, 124 CO, 311 al. 1 CPC (CH), 68 al. 2 CPC (CH), 95 al. 3 let. b CPC (CH)